Substratos para produção de rosa do deserto - Barrozo Júnior, Luiz Carlos Rodrigues (2017)
The objective of this study was to evaluate the influence of different types of substrate formulated from commercially available materials on seedling production and development of desert rose plants. In this study nine treatments were used: 1 = pinus bark; 2 = pinus bark (75%) + coconut powder (25%); 3 = pinus bark (50%) + coconut powder (50%); 4 = pinus bark (75%) + humus (25%); 5 = pine bark (50%) + humus (50%); 6 = substrate 2 (75%) + humus (25%); 7 = substrate 2 (50%) + humus (50%); 8 = substrate 3 (75%) + humus (25%); 9 = substrate 3 (50%) + humus (50%). The experimental design was completely randomized with four replicates, totaling 36 experimental units. The experiment was evaluated in three stages: 1- seedling emergence; 2- production of the seedlings in tray; 3-development of potted plants. For the evaluation of the emergency, daily seedling counts were made until the end of this process, when the percentage of emerged seedlings and the rate of emergence (IVE) were calculated. For seedling production, the following variables were considered: seedling height, stem diameter and number of leaves. Regarding the development of plants, this was evaluated in two periods: at the time of pruning, when the same variables used for seedling production were analyzed; and at the beginning of flowering, in this study the variables height of the largest branch, stem diameter and number of branches. Treatment 1 was the one that promoted a greater speed of the emergence of desert rose seedlings. With regard to seedling production, treatments 1, 2 and 3 promoted higher plant height, treatment 2 greater stem diameter and treatment 3 higher leaf number. For the development of plants the best results were observed in plants grown on substrates 2 and 3. Under the conditions in which this research was carried out, it is concluded that: For the production of desert rose seedlings the commercial substrate composed of bark of pinus (flower box). The substrate with better drainage promoted better development of desert rose.